P-order e-open Continuous Mapping in Cubic Topological Spaces - B. VIJAYALAKSHMI; M. MUTHUKALIAMMAL; G. SARAVANAKUMAR (The Bioscan, 2024)
we discuss about nearby open sets, their properties and examples of it. Moreover, we look into some of their primary properties and examples of P-cubic e-continuous in a P order cubic topological space.